Tracheal stent - Lie, Anthony. (2010)
Tracheal stenosis and tracheomalacia are two diseases that causes blockage of the airway. Surgery, which is the predominant treatment of these diseases, has high risk of mortality. Current technologies employ the use of metallic and silicone stents to support and open the airway. However, these stents are non-viable and difficult to replace or reposition. This gave rise to research in using biodegradable polymers for stenting.